Unsteady Stokes Flow Past a Shear Free Sphere - Venkatalakshmi, A. (Communications in Mathematics and Applications, 2022)
A method of solution for the problem of an arbitrary unsteady Stokes flow in the presence of a shear free sphere is discussed. The corresponding Faxén [2] relations for a shear-free sphere are derived. Some previously known results are derived as limiting cases and are detailed in an example.
Keywords: Unsteady Stokes flow; Shear free sphere; Faxén relations